2017
DOI: 10.1021/acs.jchemed.6b00694
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Chlorophyll Loss Due to Phytoremediation of Ag Nanoparticles in the First-Year Laboratory

Abstract: A two-week experiment is presented in which students can observe the impact of nanoparticles on the concentration of chlorophyll in plants. First-year students in an introductory nanotechnology laboratory course and a general chemistry laboratory course synthesized silver nanoparticles and then exposed stalks of Egeria densa (E. densa), a common waterweed, to the nanoparticle solution for 1 week. In the following session, students extracted chlorophyll from the plants and measured its concentration using a vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In a study conducted by Asghar et al [12], the researchers reported increased chlorophyll content in soya plants grown from seeds stimulated with He-Ne laser light and alternating magnetic fields. As observed by Winkelmann et al [77], silver nanoparticles can interfere with cells' biological functions due to two distinct mechanisms. A nanoparticle may be absorbed by a plant cell and start to release silver cations as products of various redox reactions.…”
Section: Elements Concentrations In Leaves Of Pumpkinmentioning
confidence: 90%
“…In a study conducted by Asghar et al [12], the researchers reported increased chlorophyll content in soya plants grown from seeds stimulated with He-Ne laser light and alternating magnetic fields. As observed by Winkelmann et al [77], silver nanoparticles can interfere with cells' biological functions due to two distinct mechanisms. A nanoparticle may be absorbed by a plant cell and start to release silver cations as products of various redox reactions.…”
Section: Elements Concentrations In Leaves Of Pumpkinmentioning
confidence: 90%
“…Application of Ag NPs led to decreased transpiration in Cucurbita pepo (Mishra et al 2014). The concentrations of Chl a and Chl b decreased in Brazilian waterweed (Egeria densa) upon exposure to Ag NPs (Winkelmann et al 2017). Treatments with Ag NPs (20-50 mg L -1 ) harmed mung plants and decreased their total Chl contents (Mahto et al 2019).…”
Section: Silver Nanoparticles (Ag Nps)mentioning
confidence: 99%